A national pharmacovigilance centre perspective on pandemic preparedness - lessons learned from the COVID-19 pandemic - van Hunsel, Florence; Kant, Agnes (Frontiers in Drug Safety and Regulation, 2025)
The SARS-CoV-2 (COVID-19) pandemic highlighted the critical role of pharmacovigilance in ensuring vaccine and drug safety. This perspective from the Netherlands Pharmacovigilance Centre Lareb outlines key experiences and lessons learned during the pandemic. Lareb managed over 233,000 individual case safety reports (ICSRs) related to COVID-19 vaccines, with a considerable proportion submitted by consumers/vaccinated persons directly. Lareb employed both spontaneous reporting and cohort event monitoring (CEM) to gain a better understanding of the safety of these vaccines in a real-world setting. Challenges included the overwhelming volume of data, limited initial access to national vaccination and healthcare registries, underreporting of adverse reactions to SARS-CoV-2 treatments, and a strain on the trained staff to perform tasks while scaling up in personnel. Lareb addressed some challenges through further automation, although more work in this area is still needed. Communication efforts were expanded with a focus on transparency and timeliness. Key recommendations for future pandemic preparedness include investing in Artificial Intelligence for further automation in the reporting process and in signal detection, looking at ways to tackle underreporting for specific associations or medicines in innovative ways and enhancing timely linkage between vaccination and healthcare data. The article underscores the importance of transparent, independent communication and the need for a resilient pharmacovigilance system capable of rapid scale-up during health crises.